In situ dispersion and polymerization of polyethylene cellulose nanocrystal‐based nanocomposites. Issue 13 (30th September 2019) - Hendren, Keith D.; Baughman, Travis W.; Deck, Paul A.; Foster, E. Johan
ABSTRACT: This study describes a novel method of forming a nanocomposite comprising cellulose nanocrystals (CNCs) as the reinforcing filler and a high‐density polyethylene (PE) matrix. The method involves covalent attachment of a metallocene catalyst, 1, 1′‐bis(bromodimethylsilyl)zirconocene dibromide 1, to the hydroxyl‐rich surfaces of the CNCs and subsequent slurry polymerization with excess alumoxane (MMAO‐12) as the cocatalyst. Polymerization proceeds with activities reaching 500 kg mol −1 atm −1 h −1, while the CNCs are simultaneously dispersed to afford robust, well‐dispersed nanocomposites. Films of these composites (about 7‐vol % CNC) showed excellent dispersal of the filler (optically translucent; no CNC aggregation observed by atomic force microscopy). The composites (about 7‐vol % CNC) also revealed an increase in Young's modulus (10–100%) and comparable yield strength relative to commercially produced PEs. The experimental simplicity of this approach suggests that our method could be scaled beyond the present laboratory scale and extended to reinforce other polyolefin grades. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48500. Abstract : A novel method for creating in situ cellulose nanocrystal (CNC)/polyethylene (PE) composites is reported. CNCs were covalently functionalized with the catalyst 1, 1′‐bis(bromodimethylsilyl)zirconocene dibromide and activated by a cocatalyst. Subsequent polymerization in the presence of ethylene resulted in a CNC/PE composite with promising clarity and an increased tensile modulus, 10–100% greater than conventional unfilled high‐density PE.